Star decompositions of suspended graphs - Farrell E.J.; De Matas C.M. (Utilitas Mathematica, 2002)
Let G be a graph and x, a component node, not in G. The suspended graph G + x is the graph formed by joining x to every node of G. A formula is given for the star polynomial of G + x. Explicit formulae are given for the suspended chain (the fan), the suspended cycle (the wheel) and the suspended star. Various results on the number of node-disjoint decompositions of these graphs into stars, are deduced.